INTENSITAS PENGUNAAN TIKTOK DAN KREATIVITAS MAHASISWA PRODI DESAIN KOMUNIKASI VISUAL - Miyarta Yasa, I Nyoman; Sinta Dewi, Ni Putu (Berajah Journal, 2025)
TikTok has become a highly popular social media platform with a strong appeal among users. Beyond serving as a space for self-expression, TikTok also functions as an important medium for fostering creativity. Therefore, this study aims to explore the influence of TikTok in this regard. The research employs a persuasive communication approach, focusing on three dimensions: cognitive, affective, and conative. Using a quantitative method, data were collected through offline questionnaires completed by 30 Visual Communication Design students from Bumigora University who are active TikTok users. The sample was selected using purposive sampling technique. The analysis results indicate that TikTok has a positive impact in supporting the development of students’ creativity.